An evaluative survey of the compliance of city and municipal libraries in Laguna with the Minimum Standards for Public Libraries - Ticzon, Ma. Criselle A.; Ramos, Marian S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study was conducted to evaluate the extent of compliance of the city and municipal libraries in Laguna with the Minimum Standards for Public Libraries formulated by the National Library of the Philippines. The descriptive survey method was used. Data collection was facilitated by personally handing out the structured questionnaires to the librarians. A brief interview with the librarians was also done at some instances in order to complete the survey.
An overall view of the study shows that the extent of compliance of the public libraries with the standards is minimal. But this is not to say that they are not functional although more areas of improvement will definitely be beneficial to libraries concerned. Almost all the aspects in the standards like staff, budget, collection, facilities and equipment and even the administration of the library need to be reviewed and evaluated in order see what has been lacking to take the necessary action on it. As the results show, the primary reason why the standards are not being met is that the librarians are not aware of the standards because the proper authorities do not implement them. Second to this are the lack of professional expertise on the part of the library staff or personnel and the lack of proper funding from the local government units. However, the librarians expressed their concern on improving the current state of the libraries.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Public libraries -- Evaluation. -- Philippines -- Laguna; Public libraries -- Administration. -- Philippines -- Laguna; Public libraries -- Standards. -- Philippines -- Laguna